2021
DOI: 10.1002/ece3.8312
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐ratio and complementarity effects simultaneously drive aboveground biomass in temperate Quercus forests through stand structure

Abstract: Forests play important roles in terrestrial ecosystems as the most important biodiversity repositories and components of the global carbon cycle (Houghton et al., 2009;King et al., 2012). Variations in the biodiversity, as well as structural and abiotic factors (e.g., climate and soil), determine forest ecosystem functioning (Ali et al., 2019a;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 104 publications
1
0
0
Order By: Relevance
“…Elevated AGBh levels stimulate LAIT expansion by providing resources for robust leaf growth, leading to a denser canopy and greater leaf coverage. Similarly, our findings support a positive relationship between SLAcwm and AGBh (Finegan et al, 2015;Ali et al, 2017;Gao et al, 2021).…”
Section: Agbh Relationships With Lait Slacwm and Srsupporting
confidence: 89%
“…Elevated AGBh levels stimulate LAIT expansion by providing resources for robust leaf growth, leading to a denser canopy and greater leaf coverage. Similarly, our findings support a positive relationship between SLAcwm and AGBh (Finegan et al, 2015;Ali et al, 2017;Gao et al, 2021).…”
Section: Agbh Relationships With Lait Slacwm and Srsupporting
confidence: 89%
“…In our analysis, we identified high importance of key-species abundance to explain ecosystem productivity and we found support for the 'mass ratio hypothesis' (Grime 1998), but we also found that trait diversity has a positive association with productivity, in line with the 'complementary resource use hypothesis' (Naeem et al 1994). A joint relevance of both hypotheses has been found repeatedly for productivity (Sonkoly et al 2019;Gao et al 2021) and other ecosystem processes (García-Palacios et al2017;Le Bagousse-Pinguet et al 2021), and countless studies exist that support each of these two hypotheses individually. It therefore appears appropriate to view the 'mass ratio hypothesis' and 'complementary resource use hypothesis' as independent axioms in the context of multifunctionality: some ecosystem functions are driven more by averages of traits while others primarily respond to trait diversity or complementarity.…”
Section: Main Textsupporting
confidence: 79%
“…On the one hand, high-mixed stands tend to exhibit greater variation in tree size differentiation compared to pure stands. In such stands, trees often compete for resources by occupying more space (Morin, 2015), driving trees to realize their growth potential, Gao et al (2021aGao et al ( , 2021b have also reported the strong positive relationship between structural diversity and above-ground biomass,,infered structural complexity may in itself increase forest growth by eupgrading complementary effect among tree species (Ishii et al 2004); on the other hand, different tree species complement each other due to the change of individual tree size, crown sizes and specifications. In more complex stand structure, trees are more likely to occupy distinct niches and efficiently utilize environmental resources, potentially enhancing complementarity, such as light capture and use efficiency (Forrester et al, 2013).…”
Section: Implications For Forest Carbon Managementmentioning
confidence: 99%